Prevalence, Risk Factors, and Negative Outcomes of Anxiety and Depressive Disorders among HIV-Infected Children and Adolescents in Uganda: CHAKA Study 2014-2017 - Mpango, Richard Stephen; Ssembajjwe, Wilber; Rukundo, Godfrey Zari; Salisbury, Tatiana Taylor; Levin, Jonathan; Gadow, Kenneth D.; Patel, Vikram; Kinyanda, Eugene (Psychiatry Journal, 2022)
Background: Children and adolescents infected with HIV/AIDS (CA-HIV) experience a considerable burden of depressive and anxiety disorders that have a tendency to persist into adulthood. The aim of this study was to determine the prevalence of anxiety, depression, and their clinical correlates among children and adolescents with HIV/AIDS (CA-HIV) in Uganda. Methods: A random sample of 1339 CA-HIV (ages 5-18 years) and their caregivers completed a standardized DSM-5- referenced psychiatric rating scale, the Child and Adolescent Symptom Inventory-5 (CASI-5). The prevalence of “anxiety and depression” was estimated at 95% confidence intervals. Logistic and ordinal regression models were fitted for the clinical correlates and clinical outcomes. Results. The overall prevalence of “any anxiety and depressive disorders” was 13.7% at 95% CI (based upon the symptom count criteria); 4.0% (95% CI) met the clinical psychiatric disorder criteria (both symptom count and functional impairment criteria). Anxiety disorder was more prevalent (9%, 95% CI) than depression (6.4%, 95% CI). Correlates of “anxiety and depressive disorders” included age of the child, caregiver’ psychological distress, caregivers’ age, child-caregiver relationship, and child’s current CD4 count (aOR1.00, 95% CI 1.02–1.05; p = 0:021). Anxiety disorders (aOR 2.58, 95% CI 1.16-5.42; p = 0:02) and depressive disorders (aOR 2.47, 95% CI 1.93–6.52; p = 0:041) were also associated with hospital admissions. Limitations: Analyses were cross-sectional; we cannot comment on the causal directions. The results are entirely based upon caregiver’ reports. Conclusions: There is an urgent need to integrate mental health services into routine HIV care for CA-HIV in sub-Saharan Africa.
Keywords: Anxiety; Depressive; Disorders; HIV-Infected Children; Adolescents; Uganda